Penerapan Sistem Manajemen Mutu Iso 9001:2008 Dalam Meningkatkan Pelayanan Publik Di Stasiun Karantina Ikan, Pengendalian Mutu Dan Keamanan Hasil Perikanan Kelas I - Saharuddin (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2024)
This research aims to determine and analyze the implementation of the ISO 9001:2008 quality management system at the Fish Quarantine Station, Quality Control and Safety of Gorontalo Class I Fishery Products and to determine and analyze the factors that are obstacles. This research uses a basic survey research approach with a qualitative descriptive research type. The results of observations and documentation studies are relevant and related to the research focus. The results of the research show that the implementation of the ISO 9001:2008 quality management system in improving public services at the Fish Quarantine Station, Quality Control and Safety of Gorontalo Class I Fishery Products has demonstrated commitment to the preparation and implementation of the ISO 9001:2008 quality management system with the principle of focusing on customers, as well as has an organizational structure and establishes job descriptions and responsibilities of personnel to ensure employee involvement in ensuring the processes required for the quality management system are established, implemented and maintained. Factors that become obstacles to implementing the ISO 9001:2008 quality management system: (a) Limited number and competency of Human Resources, especially regarding education, knowledge, expertise, skills and experience that must be possessed by officers in providing public services, (b) The determination and availability of building facilities and infrastructure, work spaces and services do not yet meet the standards as determined but can support the implementation of a series of public service delivery activities.